Evaluation and Its Methodology in Measuring the Achievement of Educational Objectives - Ahmad Mahfud Abdul Qodir (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2021)
The educational evaluation is a systematic process in collecting data, analyzing, interpreting information or data obtained by the holder in the framework of answering questions that arise for the progress and improvement of education. Evaluation as an action or process at least has three main functions namely Measuring progress, Supporting the preparation of plans, Improving or refining the process. The aim of this study is finding the relevant methods to find out the quality of students being able to find material that is in accordance with their abilities in order to create acceleration of the achievement of educational goals. The method used is a literature review method by collecting data needed from primary and secondary sources so as to create good and useful study. From the results of this study, the author found an effective and efficient way of measuring students' competencies and found techniques to detect weaknesses and strengths in their knowledge.